(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
The paper presents the results of research on the farms of «Kovalchukivske» and «Vatal» PA of Bohodukhiv district, Kharkiv region, in 2022‒2023. It was found that unstable moisture conditions in 2023 had a negative impact on the yield of drought-tolerant sunflower hybrids, reducing it by 9-22% depending on the hybrid compared to the previous year. The reason for the decrease in yields was a large amount of precipitation at the beginning of the growing season, which led to the formation of a superficial root system and an increase in the leaf surface of plants. As a result, sunflower hybrid crops became poorly blowing, which led to increased humidity in sunflower crops and the development of phomopsis and phomosis diseases. In addition, the root system of the plant, which was underdeveloped at the beginning of the growing season, did not provide the plant with soil moisture during the August heat wave, which resulted in a decrease in crop yields. Among the studied sunflower hybrids in 2023 was the hybrid NK "Condi" after the soybean predecessor.